Assessment of Students' Perceptions of the Mobile Application System for Checking Results - Adegbola, Ismail; Lawal, Odunayo (African Journal of Education and Practice, 2023)
Purpose: Students have had major difficulties in locating their results at the appropriate time due to the method of pasting results on the walls across the departments or checking through a website which required login through a web browser. These methods are not always quick, smart, and fun to access thus, creating delays and making students not be aware when the results are out. This delay serves as a hindrance to students' educational advancement and career growth. The purpose of this research is to develop a mobile result-checking Application that give students a simple way to check results with their mobile phone. Also, the research evaluates the perception and efficiency of the mobile result-checking application developed in Oyo State College of Education. Methodology: A well structure questionnaire measuring the efficiency and perception of the use of mobile result-checking application was administered to the students. The analyses were performed using SPSS. The relationship between categorical variables was summarized using frequency distribution and the Fisher exact test. Findings: The implemented mobile result-checking application works effectively on all platforms and phone brands. The perceptions and experiences of the students with the Application were positive. The features of the application were highly rated by students. A favourable user experience, positive reviews, and a user-friendly interface all contributed to the students' adoption of the application for checking their results. Unique Contribution to Theory, Practice and Policy: This research has made a meaningful contribution to the Federal Government of Nigeria Tertiary Education Trust Fund digital literacy policy of transacting educational business via digital devices.